A Novel Secreted Protein-Related Gene Signature Predicts Overall Survival and Is Associated With Tumor Immunity in Patients With Lung Adenocarcinoma - Chen, Shuaijun; Zhang, Jun; Li, Qian; Xiao, Lingyan; Feng, Xiao; Niu, Qian; Zhao, Liqin; Ma, Wanli; Ye, Hong (Frontiers in Oncology, 2022)
Secreted proteins are important proteins in the human proteome, accounting for approximately one-tenth of the proteome. However, the prognostic value of secreted protein-related genes (SPRGs) has not been comprehensively explored in lung adenocarcinoma (LUAD). In this study, we screened 379 differentially expressed secretory protein genes (DESPRGs) by analyzing the expression profile in patients with LUAD from The Cancer Genome Atlas (TCGA) database. Following univariate Cox regression and least absolute shrinkage and selection operator method (LASSO) regression analysis, 9 prognostic SPRGs were selected to develop secreted protein-related risk score (SPRrisk), including CLEC3B, C1QTNF6, TCN1, F2, FETUB, IGFBP1, ANGPTL4, IFNE, and CCL20. The prediction accuracy of the prognostic models was determined by Kaplan-Meier survival curve analysis and receiver operating characteristic (ROC) curve analysis. Moreover, a nomogram with improved accuracy for predicting OS was established based on independent prognostic factors (SPRrisk and clinical stage). DESPRGs were validated by quantitative real-time PCR (qRT-PCR) and enzyme-linked immunosorbent assay (ELISA) by using our clinical samples and datasets. Our results demonstrated that SPRrisk can accurately predict the prognosis of patients with LUAD. Patients with higher risk had lower immune, stromal, and ESTIMATE scores and higher tumor purity. Higher SPRrisk was also negatively associated with the abundance of CD8+ T cells and M1 macrophages. In addition, several genes of the human leukocyte antigen (HLA) family and immune checkpoints were expressed in low levels in the high SPRrisk group. Our results provided some insights into assessing individual prognosis and choosing personalized treatment modalities.